2011
DOI: 10.1007/s11269-011-9889-8
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Delivery Assessment for a Transboundary Mediterranean Catchment: The Example of Nestos River Catchment

Abstract: Nestos River flows through Bulgaria and Greece and discharges into the North Aegean Sea. Its total catchment area is around 6,200 km 2 , while the mean annual precipitation and runoff are 680 mm and 40 m 3 /s, respectively. The Hellenic part of the catchment has undergone a substantial hydroelectric development, since two dams associated with major hydropower pumped-storage facilities are in operation. The main objective of the paper is to assess the expected sediment delivery of Nestos R. at the uppermost Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 45 publications
1
17
0
3
Order By: Relevance
“…The first one, by Arévalo (2008), uses USLE and RUSLE models Smith 1965, 1978), which are among the most popular methodologies to study soil erosion (e.g. Brath et al, 2002;Zarris et al, 2011). Applying the RUSLE equation and a modification of the USLE model, Arévalo found an average soil erosion between 9.4 and 10.6 Mg ha -1 year -1…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one, by Arévalo (2008), uses USLE and RUSLE models Smith 1965, 1978), which are among the most popular methodologies to study soil erosion (e.g. Brath et al, 2002;Zarris et al, 2011). Applying the RUSLE equation and a modification of the USLE model, Arévalo found an average soil erosion between 9.4 and 10.6 Mg ha -1 year -1…”
Section: Introductionmentioning
confidence: 99%
“…In the Entrepeñas Reservoir -whose maximum water level area includes the Pareja Limno-reservoir-, sedimentation studies revealed that it is filled up at a rate of 0.5% per year (Palau Ybars, 2002). This value can be considered low, since for many reservoirs worldwide annual storage capacity loss can go up to 5% (de Vente et al, 2005;Zarris et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…), which is low compared to those reported for many reservoirs elsewhere (around 4%–5%, and even above 6% in some Mediterranean basins; Palau Ybars ; Zarris et al . ). The low sedimentation rate is related to the low sediment delivery ratio (2.2%–3.8%) observed in the Ompólveda River basin (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The annual storage capacity of many reservoirs may decrease by up to 4 or 5%, and the entire storage capacity may be lost after only 25–30 years (Zarris et al . ). Spain is one of the countries most severely affected by soil erosion (Solé Benet ), with signs of high soil loss being observed in the catchment of the Pareja Limno‐reservoir.…”
Section: Methodsmentioning
confidence: 97%
“…Due to the lack of detailed precipitation values the Rainfall Erosivity Factor (R) was estimated using the empirical Van der Knijff et al, (2000) equation. The choice was based on a literature review (Sigalos et al, 2010;Zarris et al, 2011). Similarly, the lack of soil properties (granulometry, organic matter content etc.)…”
Section: Results and Discusionmentioning
confidence: 99%